Sharpening the focus on occupational safety and health in nanotechnology - Schulte, Paul; Geraci, Charles; Zumwalde, Ralph; Hoover, Mark; Castranova, Vincent; Kuempel, Eileen; Murashov, Vladimir; Vainio, Harri; Savolainen, Kai (Scandinavian Journal of Work, Environment & Health, 2008)
Increasing numbers of workers are involved with the production, use, distribution, and disposal of nanomaterials. At the same time, there is a growing number of reports of adverse biological effects of engineered nanoparticles in test systems. It is useful, at this juncture, to identify critical questions that will help address knowledge gaps concerning the potential occupational hazards of these materials. The questions address (i) hazard classification of engineered nanoparticles, (ii) exposure metrics, (iii) the actual exposures to the different engineered nanoparticles in the workplace, (iv) the limits of engineering controls and personal protective equipment with respect to engineered nanoparticles, (v) the kinds of surveillance programs that may be required at workplaces to protect potentially exposed workers, (vi) whether exposure registers should be established for workers potentially exposed to engineered nanoparticles, and, (vii) whether engineered nanoparticles should be treated as “new” substances and evaluated for safety and hazards?
Keywords: discussion paper; engineering; exposure; hazard; nanoparticle; nanotechnology; occupational health; occupational safety; occupational safety and health; risk